2017
DOI: 10.1186/s13046-017-0589-y
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome activation promotes inflammation-induced carcinogenesis in head and neck squamous cell carcinoma

Abstract: BackgroundNLRP3 inflammasome acts as a danger signal sensor that triggers and coordinates the inflammatory response. However, the roles of NLRP3 inflammasome in the tumorigenesis and development of cancer stem cells (CSCs) of squamous cell carcinoma of the head and neck (SCCHN) remain ambiguous.MethodsIn our study, tissue microarrays, ELISA, sphere-forming assay, colony formation assay and Western blot analysis were performed to evaluate the effect of NLRP3 inflammasome on the development of CSCs in human SCCH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 47 publications
3
86
0
Order By: Relevance
“…Several specific inhibitors, such as MCC950, CY‐09, arglabin, and glyburide, have been recently developed or identified to target NLRP3 inflammasome inhibition . The application of these specific NLRP3 inflammasome inhibitors has demonstrated therapeutic effects in various inflammatory disease mouse models, including models of myocardial infarction, fulminant hepatitis, steatohepatitis, lupus nephritis, atherosclerosis, Alzheimer's disease, brain injury, inflammatory bowel diseases, acute colitis, and carcinoma In allergic diseases, the application of MCC950 reduces skin and airway inflammation in mouse models of allergic dermatitis and asthma . More recently, 2 studies have shown that the targeted inhibition of NLRP3 inflammasomes with a specific inhibitor decreased IL‐1β and TH2 cytokines and inhibited HDM‐induced AHR and steroid‐resistant asthma in a mouse model .…”
Section: Resultsmentioning
confidence: 99%
“…Several specific inhibitors, such as MCC950, CY‐09, arglabin, and glyburide, have been recently developed or identified to target NLRP3 inflammasome inhibition . The application of these specific NLRP3 inflammasome inhibitors has demonstrated therapeutic effects in various inflammatory disease mouse models, including models of myocardial infarction, fulminant hepatitis, steatohepatitis, lupus nephritis, atherosclerosis, Alzheimer's disease, brain injury, inflammatory bowel diseases, acute colitis, and carcinoma In allergic diseases, the application of MCC950 reduces skin and airway inflammation in mouse models of allergic dermatitis and asthma . More recently, 2 studies have shown that the targeted inhibition of NLRP3 inflammasomes with a specific inhibitor decreased IL‐1β and TH2 cytokines and inhibited HDM‐induced AHR and steroid‐resistant asthma in a mouse model .…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory microenviroment was believed to help the malignant transformation of normal stem or progenitor cells toward CSCs. Huang, Chen, et al () demonstrated upregulation of NLRP3 inflammasome was associated with CSCs self‐renewal activation in head and neck squamous cell carcinoma (HNSCC). Higher level of systemic Inflammation Response Index (SIRI) was associated with CD44 + CSCs scores in gastric cancer patients and predict unfavorable clinical outcomes (Li, Lan, et al, ).…”
Section: Nf‐κb Stimulated Chronic Inflammation Promotes Cancer Stem Cmentioning
confidence: 99%
“…This meta-analysis on the prognostic value of in ammasome molecules included 14 studies with a total of 677 patients. The expression of in ammasome molecules was found to be a controversial prognostic factor for the OS, DFS, and RFS of HNC patients (34)(35)(36)(37)(38). Although the current view is that in ammasome molecules may be important predictors of a poor prognosis in HNC (36), we found that higher expression of in ammasome molecules was associated with longer RFS of HNC patients.…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 55%